The role of an attachment style in COVID-19 vaccine hesitancy among high school learners in the Johannesburg East Region of the Gauteng Province - Maluka, Antonette Caron (My University, 2025)
The purpose of this study was to investigate the relationship between attachment styles and COVID-19 vaccine hesitancy among high school learners in the Johannesburg East region. Its aim was to understand how attachment styles affect health-related decision-making. A quantitative cross-sectional survey design was employed, utilising a sample of 303 participants. The study used established measures such as the Experiences in Close Relationships Scale—Revised Child Bried Version (ECR-RC Brief Version) to assess attachment styles; and self-constructed vaccination items to evaluate participants' attitudes towards COVID-19 vaccination. Data were analysed using logistic regression to explore the correlations between attachment styles as well as gender and age, and vaccine hesitancy. The results indicated that none of the independent variables reached statistical significance in their relationship vaccine hesitancy. Although students with anxious attachment styles exhibited tendencies towards higher vaccine hesitancy, and those with secure attachment styles demonstrated a greater willingness to vaccinate, these differences did not reach statistical significance. These findings suggest that while psychological factors like attachment styles may be relevant, they may not be the primary determinants of vaccine hesitancy among adolescents.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2025
Keywords: Attachment styles; Vaccine hesitancy; COVID-19; High school learners; Johannesburg East; Attachment behavior; Dependency; High school students -- South Africa -- Gauteng; COVID-19 vaccines -- South Africa -- Gauteng